2011
DOI: 10.1029/2011gl047036
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol nucleation induced by a high energy particle beam

Abstract: [1] We have studied sulfuric acid aerosol nucleation in an atmospheric pressure reaction chamber using a 580 MeV electron beam to ionize the volume of the reaction chamber. We find a clear contribution from ion-induced nucleation and consider this to be the first unambiguous observation of the ion-effect on aerosol nucleation using a particle beam under conditions that resemble the Earth's atmosphere. By comparison with ionization using a gamma source we further show that the nature of the ionizing particles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 26 publications
(34 reference statements)
1
50
0
Order By: Relevance
“…It is hypothesised that if some of these CCN are created through cosmic ray ionisation then global CCN could be influenced by the cosmic ray ionisation rate. The nucleation rate has been shown experimentally to increase with ion concentrations (Kirkby et al, 2011;Enghoff et al, 2011). Pierce and Adams (2009a) found that the effect of changes in cosmic rays over a solar cycle on CCN concentrations would be two orders of magnitude too small to account for observed changes in cloud properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesised that if some of these CCN are created through cosmic ray ionisation then global CCN could be influenced by the cosmic ray ionisation rate. The nucleation rate has been shown experimentally to increase with ion concentrations (Kirkby et al, 2011;Enghoff et al, 2011). Pierce and Adams (2009a) found that the effect of changes in cosmic rays over a solar cycle on CCN concentrations would be two orders of magnitude too small to account for observed changes in cloud properties.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical correlation studies are inconclusive and lead to contradictory results largely because the contemporary fast expansion of the anthropogenic factor makes it difficult to study the natural variability of the terrestrial system, including the solar factor, by means of statistical/phenomenological methods. Direct laboratory and in situ experiments (Kulmala et al, 2010;Kirkby et al, 2011;Enghoff et al, 2011) suggest that enhanced ionization may lead to aerosol particle formation in the realistic conditions, but this effect is small. There are also some global aerosol microphysics model studies testing the sensitivity of cloud condensation nuclei (CCN) concentration to the changes in nucleation that might occur due to changes in cosmic rays.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence for a microphysical mechanism was first reported in 2007 [10] and further experiments have recently added to its credibility [11,12]. These experiments initially showed that an increase in ionization leads to an increase in the formation of ultrafine aerosols (≈ 3 nm), but in the real atmosphere such small particles have to grow by coagulation and intake of condensable gases to become cloud condensation nuclei (CCN) (> 50 nm) in order to have an effect on clouds [13, chapter 17].…”
mentioning
confidence: 99%